Hormonálna antikoncepcia a jej komplikácie - Fabian, R (Ceskoslovenska gynekologie, 1987)
A group of 230 women mostly in the 20-30 age range were prescribed the steroid contraceptives Neogest, Norbiogest, Monogest, Non-Ovlon, and Yermonil. 15 women had painful irregular menstruation. 12 women had undergone abortion, and 6 had had a spontaneous miscarriage in the first trimester. Neogest, a one-phase preparation, was used by 28 women. There were 4 cases of menstrual disorders (oligomenorrhea) within 2 years of use and the pills were discontinued. There was 1 case of hypomenorrhea and 1 case of pregnancy with eutocia. Norbiogest, a predominantly gestagen-containing sequential, 2-phase preparation was used by 106 women for 1-10 years. 15 complications occurred (14.1%) consisting of hypo-, oligo-, and amenorrhea, menstrual disorders (2 cases), and lower abdominal pain (6 cases). A liver test was positive in 1 woman who used Norbiogest for 4 years. Monogest, a gestagen preparation for continuous use, was used by 20 women with 4 instances of missed menstruation. 1 case of longer amenorrhea and 1 case of irregular bleeding occurred, manifesting mostly as metrorrhagia. Non-Ovlon, a one-phase preparation, was used by 52 women. After 2 years of use, liver tests became positive. The pill was discontinued, and the tests became negative. Yermonil, a one-phase combined product, was used by 24 women without complications, although 2 women decided to quit using it. There were a total of 25 complications in the sample amounting to 10.8%.
Keywords: Hepatic Effects; Research Methodology; Physiology; Female; Europe; ženské pohlaví; Oral Contraceptives, Combined--side effects; Biology; Abortion, Spontaneous; Family Planning; lidé; Abortion, Induced; Contraception Research; Contraception; kontraceptiva orální hormonální; Fertility Control, Postconception; Oral Contraceptives, Phasic--side effects; Diseases; Humans; Contraceptives, Oral, Hormonal; Oral Contraceptives--side effects; Menstruation Disorders; Contraceptive Agents--side effects; Pregnancy Complications; Clinical Research; Czechoslovakia; Contraceptive Agents, Female--side effects; Contraceptive Methods--side effects; Developed Countries; Eastern Europe